Nerve stepping stone has minimal impact in aiding regeneration across long acellular nerve allografts. Issue 2 (6th June 2017) - Yan, Ying; Hunter, Daniel A.; Schellhardt, Lauren; Ee, Xueping; Snyder‐Warwick, Alison K.; Moore, Amy M.; Mackinnon, Susan E.; Wood, Matthew D.
ABSTRACT: Introduction: Acellular nerve allografts (ANAs) yield less consistent favorable outcomes compared with autografts for long gap reconstructions. We evaluated whether a hybrid ANA can improve 6‐cm gap reconstruction. Methods: Rat sciatic nerve was transected and repaired with either 6‐cm hybrid or control ANAs. Hybrid ANAs were generated using a 1‐cm cellular isograft between 2.5‐cm ANAs, whereas control ANAs had no isograft. Outcomes were assessed by graft gene and marker expression ( n = 4; at 4 weeks) and motor recovery and nerve histology ( n = 10; at 20 weeks). Results: Hybrid ANAs modified graft gene and marker expression and promoted modest axon regeneration across the 6‐cm defect compared with control ANA ( P < 0.05), but yielded no muscle recovery. Control ANAs had no appreciable axon regeneration across the 6‐cm defect. Discussion: A hybrid ANA confers minimal motor recovery benefits for regeneration across long gaps. Clinically, the authors will continue to reconstruct long nerve gaps with autografts. Muscle Nerve 57 : 260–267, 2018